Teachers’ Characteristics, ICT Use and Educational Outcomes - Joshi, Bishnu Maya; Khatiwada, Shambhu Prasad (Teacher Half-Yearly Journal, 2025)
The integration of Information and Communication Technology (ICT) into education has gained momentum due to its potential to revolutionize teaching and learning. However, the success of ICT implementation relies heavily on various factors related to teachers' attitudes, skills, and beliefs toward technology use. This study sought to examine the relationship between teachers' characteristics, their use of ICT, and its impact on educational outcomes. A systematic review was conducted, identifying 17 high-quality studies that met rigorous methodological criteria. The analysis revealed that teachers' digital competence, alongside their perceptions of the usefulness of ICT tools, were significant predictors of effective technology integration in the classroom. Furthermore, teacher motivation, mindset, and opportunities for collaboration emerged as critical drivers for successful ICT adoption. The study also underscored the pivotal role the COVID-19 pandemic played in accelerating teachers' acquisition of digital skills, emphasizing the urgent need for expanded access to technology and professional development programs aimed at enhancing online instructional capabilities. These findings point to the necessity of addressing not only individual teacher characteristics but also institutional and systemic factors to ensure the successful integration of ICT in education. A holistic approach is essential to improve teaching practices and maximize the benefits of ICT in educational settings.